Play and Recreation, Health and Wellbeing - Evans, Bethan; Horton, John.; Skelton, Tracey; SpringerLink (Online service) (Singapore : Springer Singapore(Imprint), 2016)
Geographies of children and young people is a rapidly emerging sub-discipline within human geography. There is now a critical mass of established academic work, key names within academia, growing numbers of graduate students and expanding numbers of university level taught courses. There are also professional training programmes at national scales and in international contexts that work specifically with children and young people. In addition to a productive journal of Children's Geographies, there's a range of monographs, textbooks and edited collections focusing on children and young people published by all the major academic presses then there is a substantive body of work on younger people within human geography and active authors and researchers working within international contexts to warrant a specific Major Reference Work on children's and young people's geographies. The volumes and sections are structured by themes, which then reflect the broader geographical locations of the research.
Keywords: Human geography; Childhood, Adolescence and Society